The Dynamics of biodiversity change after deforestation (Revista Científica Ciencias Naturales y Ambientales, 2017)
The many changes that forests have suffered over the last century have led to biodiversity loss around the planet. In order to understand these processes and try to predict future biological diversity loss, spatial comparisons have commonly been used. This research uses spatial and temporal data aiming to understand better the dynamics of these changes caused by deforestation. A meta-Analysis was conducted compiling information from 13 studies using before-after-controlimpact design (BACI) to examine abundance response to deforestation. The results show clearly that biodiversity tends to decline in the five years after forest loss, though losses are not significant within the first two years. It was also found that the effects of deforestation on species abundance varied significantly among taxonomic groups, physical level species occupy in the ecosystem, type of disturbance, type of perturbation, and constancy in the surveys. The outcome of this research agrees with results of studies with spatial comparisons, though it is not yet possible to conclude which is best to predict biodiversity changes. However, these findings deepen our understanding of the complexity of biodiversity change and deforestation and emphasize importance of generating more studies that include temporal data.
Keywords: Biodiversity; BACI; Changes; Deforestation